Pathogenderived resistance using a viral nucleocapsid gene confers only partial nondurable protection in peanut against peanut bud necrosis virus - Rao, S.C.; Bhatnagar-Mathur, P.; Kumar, P. Lava; Reddy, S.; Sharma, K. (Springer, 2013)
Genetic engineering of peanut (Arachis hypogaea L.) using the gene encoding for the nucleocapsid protein (N gene) of peanut bud necrosis virus (PBNV; genus Tospovirus, family Bunyaviridae) was used to impart resistance to bud necrosis disease in peanut (PBND), a disease for which no durable resistance is available in the existing germplasm. Over 200 transgenic lines of peanut var. JL 24 were developed for which integration and expression of the transgenes was confirmed by PCR, Southern hybridization, RT-PCR and western blot analysis. The T1 and T2 generation transgenic plants were assayed through virus challenge in the greenhouse by using mechanical sap inoculation at 1:100 and 1:50 dilutions of PBNV, and they showed varying levels of disease incidence and intensity. Greenhouse and field evaluation with T2 generation plants indicated somewhat superior performance of the three transgenic events that showed considerable reduction in disease incidence. However, only one of these events showed over 75 % reduction in disease incidence when compared to the untransformed control, indicating partial and non-durable resistance to PBND using the viral N-gene.